Circular Bioeconomy and Valorization of Waste from the Apple Processing Industry; [Bioeconomía Circular y Valorización de Residuosde la Industria Procesadora de la Manzana] - Marchant-Silva, R (Universidad de Tarapaca, 2022)
At present, society values the circular bioeconomy, since it contributes to the reduction of negative externalities, which arise from the operation of certain industries, which generate waste, are harmful to the environment and, on the contrary, the valorization of the waste, contributes to improving the competitiveness of the industry. In this work, new businesses developed from the use of apple pomace are identified and validated. For this purpose, a portfolio of viable pomasa valorization options was created, based on a contextual analysis, the application of the Product-Market adjustment and the participation of a focus group. Pomasa in the form of flour can be incorporated in the production of snacks, antioxidant drinks and yogurt. The sum of the NPV of these businesses reaches USD 11.77 million, using 1.3% of pomasa generated annually in Chile. This study contributes to the validation of the circular business model in a relevant sector of the Chilean economy. © 2022, Universidad de Tarapaca. All rights reserved.